Integer and Fractional-Order Sliding Mode Control Schemes in Wind Energy Conversion Systems: Comprehensive Review, Comparison, and Technical Insight - Irfan Sami; Shafaat Ullah; Laiq Khan; Ahmed Al-Durra; Jong-Suk Ro (Fractal and Fractional, 2022)
The technological development in wind energy conversion systems (WECSs) places emphasis on the injection of wind power into the grid in a smoother and robust way. Sliding mode control (SMC) has proven to be a popular solution for the grid-connected WECS due to its robust nature. This paper reviews the enhancement trends in the integer-order SMC (IOSMC) and fractional-order SMC (FOSMC) schemes reported in reputed journals over the last two decades. This work starts with a mathematical description of the wind turbine, generators, grid, and SMC and its variants available in literature. A comprehensive literature review is tabulated that includes the proposed errors, sliding surfaces, typologies, and major outcomes. Moreover, a comparative analysis of the integer-order and fractional-order SMC and its variants is also presented in this paper. This paper will provide insight for the researcher working in the WECS and will serve them in the selection and exploration of the most appropriate control schemes for quality wind power extraction. The concise mathematical proofs of the IOSMC, FOSMC and their variants will also serve the researchers in selecting the relevant sliding surfaces control laws for their research tasks. This paper also provides a comparative analysis of IOSMC, FOSMC, and fuzzy-FOSMC in terms of chattering reduction, robustness, and computational complexities using mathematical theories, simulation carried out in Matlab/Simulink, and a processor in the loop (PIL)-based experimental environment.